Microglia activation in a pediatric rabbit model of tuberculous meningitis - Elizabeth W. Tucker; Supriya Pokkali; Zhi Zhang; Vincent P. DeMarco; Mariah Klunk; Elizabeth S. Smith; Alvaro A. Ordonez; Marie-France Penet; Zaver Bhujwalla; Sanjay K. Jain; Sujatha Kannan (The Company of Biologists, 2016)
Central nervous system (CNS) tuberculosis (TB) is the most severe form of extra-pulmonary TB and disproportionately affects young children where the developing brain has a unique host response. New Zealand white rabbits were infected with Mycobacterium tuberculosis via subarachnoid inoculation at postnatal day 4-8 and evaluated until 4-6 weeks post-infection. Control and infected rabbit kits were assessed for the development of neurological deficits, bacterial burden, and postmortem microbiologic and pathologic changes. The presence of meningitis and tuberculomas was demonstrated histologically and by in vivo magnetic resonance imaging (MRI). The extent of microglial activation was quantified by in vitro immunohistochemistry as well as non-invasive in vivo imaging of activated microglia/macrophages with positron emission tomography (PET). Subarachnoid infection induced characteristic leptomeningeal and perivascular inflammation and TB lesions with central necrosis, a cellular rim and numerous bacilli on pathologic examination. Meningeal and rim enhancement was visible on MRI. An intense microglial activation was noted in M. tuberculosis-infected animals in the white matter and around the TB lesions, as evidenced by a significant increase in uptake of the tracer 124I-DPA-713, which is specific for activated microglia/macrophages, and confirmed by quantification of Iba-1 immunohistochemistry. Neurobehavioral analyses demonstrated signs similar to those noted in children with delayed maturation and development of neurological deficits resulting in significantly worse composite behavior scores in M. tuberculosis-infected animals. We have established a rabbit model that mimics features of TB meningitis in young children. This model could provide a platform for evaluating novel therapies, including host-directed therapies, against TB meningitis relevant to a young child's developing brain.